2008
DOI: 10.1111/j.1365-2958.2008.06113.x
|View full text |Cite
|
Sign up to set email alerts
|

DrRRA: a novel response regulator essential for the extreme radioresistance of Deinococcus radiodurans

Abstract: SummaryTwo-component systems are predominant signal transduction pathways in prokaryotes, and also exist in many archaea as well as some eukaryotes. A typical TCS consists of a histidine kinase and a cognate response regulator. In this study, a novel gene encoding a response regulator (we designate it drRRA) is identified to be essential for the extreme radioresistance of Deinococcus radiodurans. DrRRA null mutant (we designate it MR) is sensitive to gamma-radiation compared with the wild-type strain. Transcri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
100
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 91 publications
(104 citation statements)
references
References 39 publications
(44 reference statements)
4
100
0
Order By: Relevance
“…Our previous studies showed that PprI and RecX participated in the regulation of RecA as positive and negative regulators, respectively, in response to ␥ radiation (19,42). Interestingly a novel protein named Deinococcus radiodurans Response Regulator A (DrRRA) (DR2418) has also been identified for its positive role in the control of RecA expression under stressfree growth conditions, although its expression was constant under radiation stresses regardless of the presence of DrRRA (23). This may suggest that there is a novel regulatory mechanism of RecA in this bacterium.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies showed that PprI and RecX participated in the regulation of RecA as positive and negative regulators, respectively, in response to ␥ radiation (19,42). Interestingly a novel protein named Deinococcus radiodurans Response Regulator A (DrRRA) (DR2418) has also been identified for its positive role in the control of RecA expression under stressfree growth conditions, although its expression was constant under radiation stresses regardless of the presence of DrRRA (23). This may suggest that there is a novel regulatory mechanism of RecA in this bacterium.…”
Section: Discussionmentioning
confidence: 99%
“…8). Superoxide dismutase and catalase activities are decreased and RecA and PprA levels are reduced in the DrRRA gene mutant (645).…”
Section: Continued On Following Pagementioning
confidence: 99%
“…Although recA is strongly induced after irradiation, pprI is constitutively expressed, with no postirradiation induction (368). Under nonstress conditions, the transcriptional regulator DrRRA positively controls the expression of RecA, with no effect under radiation stress (645). The transcriptional regulator DdrO may be responsible for the induction of recA in gamma-irradiated cells (383).…”
Section: Recombinational Processes In D Radiodurans Dna Repairmentioning
confidence: 99%
See 1 more Smart Citation
“…A pool of distinctive genes involved in the stress response has been investigated to explain the extreme resistance of D. radiodurans [17][18][19][20][21][22][23]. Among them, two regulators are noteworthy.…”
mentioning
confidence: 99%